USE OF A STRAIN OF MICROSCOPIC FUNGUS ASPERGILLUS TERREUS 49/10-1 FOR DEGRADATION OF OIL - Zhagipar , F.S.; Nechay , N.L.; Moldagulova , N.B.; Yagofarova, A.Ya.; Berdimuratova , K.T.; Kakimzhanova , A.A. (Eurasian Journal of Applied Biotechnology, 2017)
Oil and oil products are among the main and widespread sources of pollution of water and terrestrial ecosystems. Accidents in oil production can pollute both water and soil ecosystem; in the latter, the pollution can change the soil structure and its redox potential, degrade living conditions of plants and animals, under mine trophic transfer, and block the natural oxygen cycle. A large number of oil fields are situated in the Kazakhstan Republic, especially in the western areas of the country. Oil production and transportation accidents occur regularly and have a severe and deleterious effect on the environment and on wildlife. Therefore, searching for effective bioremediation methods for water and soil is vital. Hydrocarbons can be degraded by microbial activity, for example, by fungal species that can use oil and oil products as a source of carbon and energy. The aim of our work is to characterize the ability of the microscopic fung us Aspergillus terreus 49/10-1 to degrade oil and oil products in soil and water. This strain was isolated from soil of the Caspian Sea and shows high efficiency in bioremediation of oil-contaminated water and soil. More than 89.5% of oil and oil products in water was degraded; in soil, more than 40% was degraded.